Small and large fiber neuropathy in adults with myotonic dystrophy type 1 - Solbakken, Gro; Løseth, Sissel; Frich, Jan C.; Dietrichs, Espen; Ørstavik, Kristin (Frontiers in Neurology, 2024)
Introduction: Myotonic Dystrophy type 1 (DM1) is an inherited neuromuscular disorder that affects multiple organs. In this study, we investigated symptoms of pain and presence of small and large fiber neuropathy in the juvenile and adult form of DM1. Method: 20 genetically verified DM1 patients were included. Pain was assessed, and neurological examination and investigations of the peripheral nervous system by quantification of small nerve fibers in skin biopsy, quantitative sensory testing and nerve conduction studies were performed. Results from skin biopsies were compared to healthy controls. Result: 17 patients reported chronic pain. Large and/or small fiber abnormalities were present in 50% of the patients. The intraepidermal nerve fiber density was significantly lower in the whole group of patients compared to healthy controls. Conclusion: Small-fiber neuropathy might be an important cause of pain in DM1.